PENGARUH RASIO KEUANGAN TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN SEKTOR TRADE, SERVICE AND INVESTMENT YANG TERDAFTAR DI BEI - Siti Sara -; Erinta Sijabat -; Putri Husyada Fi’lma -; Febti Latreia Missi -; Dwita Sakuntala - (JEBIM Prima, 2021)
This study aims to determine the financial ratios represented by the liquidity ratio, activity ratio, solvency ratio, profitability ratio to dividend payout ratio. Data collection techniques using purposive sampling and obtained as many as 21 samples of companies from 132 populations of companies in the trade, service, and investment sectors listed on the Indonesia Stock Exchange (BEI). The analysis technique uses multiple linear regression. Based on the results of the coefficient test, the R square value of 0.141 indicates that the correlation or closeness of the relationship between the liquidity ratio, activity ratio, solvency ratio, profitability ratio and dividend payout ratio is only 14.1%. The Adjusted R Square value of 0.097 indicates that the liquidity ratio, activity ratio, solvency ratio, profitability ratio explains the variable to the dividend payout ratio of 9.7%. The F test shows that the value of Fcount> Ftable (3,235> 2.49) so that simultaneously the quick ratio, Total Asset Turn Over, Debt to Asset Ratio, Return On Equity have an effect on the dividend payout ratio in companies in the trade, service and investment sectors. In the t test results, only the Profitability Ratio (Return On Equity) variable has a positive and significant effect on the dividend payout ratio, which is 0.048.